OPTIMASI ALGHORITMA BREADTH FIRST SEARCH PADA GAME ENGINE 3D THIRD PERSON SHOOTER MAZE BERBASIS AGEN CERDAS ANDROID - Astrid Novita Putri (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Game is currently very popular in the community at large, one of which is the game third person shooter (TPS) which can be run through a mobile phone or computer, making it very easy and affordable, one thrid person shooter game 3D maze.The labyrinth is a game to find the right path to achieve the objectives which the way players experience many obstacles to destination, so spend a lot of time,then in need of a settlement in order to facilitate the player in completing the levels on every obstacle, in need of a alghoritm Breadth First Search for ease in completing permainan.Cara employment levels every alghoritm Breadth First Search is a search method that starts with the roots off the road to the next.This search is done by looking at all the nodes or vertices have the same level to determine the final outcome at that level,if they do not find the will to move to the next level. so that the process backtrackto re-find the right path to achieve goals the appropriate time. Keyword: Games, Third person, Shooter, Maze, Breadth First Search.